Publication rates and characteristics of PGY2 psychiatric pharmacy resident research projects - Dayton L. Antley, PharmD, BCPS, BCPP; Leigh Anne Nelson, PharmD, BCPP; Carrie R. Kriz, MS; Courtney A. Iuppa, PharmD, BCPP; Shelby E. Lang, PharmD, BCPP; Nicole A. Gramlich, PharmD, BCPP; Ellie S. R. Elliott, PharmD, BCPP; Roger W. Sommi, PharmD, BCPP, FCCP (American Association of Psychiatric Pharmacists, 2023)
Introduction: To describe the publication rates and characteristics of PGY2 psychiatric pharmacy residency projects presented as a poster presentation at the annual meetings of the College of Psychiatric and Neurologic Pharmacists (CPNP) from 2002 to 2018. (As of 2022 the organization is under the name, American Association of Psychiatric Pharmacists.) Methods: CPNP abstracts from even years were strategically searched in PubMed, Ovid MEDLINE, and Google Scholar. If a publication was identified, additional data were collected for characterization, including study information, journal information, author information, institutional affiliation, publication year, and time to publication. Results: A total of 348 abstracts were evaluated. Publication in a journal was achieved for 60 projects (17.2%), with publication rates decreasing from 2012 to 2018. The mean time to publication was 17.3 months after completion of the residency, with most projects published at 8 months. More than half (51.7%) of these projects were published in a psychiatric pharmacy journal affiliated with CPNP. Study designs were predominantly retrospective, observational, cohort studies with a focus on evaluation of a drug therapy outcome. The PGY2 resident was the first author in 90% of the publications. Forty percent included other health care professionals outside of pharmacy as a coauthor. PGY2 residencies affiliated with academic institutions had overall higher publications rates. Discussion: Publication rates for PGY2 psychiatric pharmacy residency projects are low and are decreasing over time despite an increasing number of PGY2 psychiatric pharmacy residency programs. This publication rate is lower than that reported in the literature for PGY2 critical care residency programs. The downward trend of publication rates for PGY2 psychiatric pharmacy residency projects is concerning.